2006
DOI: 10.1111/j.1470-6431.2006.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Young Europeans abroad in Scotland: an exploration of how their attitudes to consumer credit reflect dimensions of culture

Abstract: Nineteen young Europeans from across the Continent took part in in‐depth interviews where a wide range of consumer‐related issues were explored. These issues ranged from specific consumer behaviours and consumer value gained to consumer protection and other aspects of policy. Respondents were postgraduates studying at Scottish universities or young professionals currently working in Scotland. The interviews were structured around a number of key themes that were developed both from the literature and from an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Similar observations have been made by researchers and specialists from other countries in both Europe and North America (e.g. McKinnon and Schröder, ; O'Loughlin and Szmigin, ; Cummins et al ., ; Bankruptcy Legal Group, ).…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Similar observations have been made by researchers and specialists from other countries in both Europe and North America (e.g. McKinnon and Schröder, ; O'Loughlin and Szmigin, ; Cummins et al ., ; Bankruptcy Legal Group, ).…”
supporting
confidence: 87%
“…Indeed, beginning their adult life, students or young workers often have a less stable financial situation (Lokken Worthy et al ., ) and generally show a lower level of literacy in regard to their personal finances (e.g. Lachance et al ., ; McKinnon and Schröder, ). Moreover, young adults are more likely than others to engage in more risky financial behaviours (Nelson and Barry, ; National Foundation for Credit Counseling, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although they considered themselves as sufficiently empowered, respondents spent some time considering the position of more vulnerable consumers in society. There were some cultural differences in the attribution of blame, with Scandinavians tending to hold unscrupulous providers responsible and CEE and Southern Europeans criticizing a lack of family and community support (see also McKinnon and Schröder, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For goods where evaluation prior to purchase is difficult, such as used cars, legal advice and home repairs, one‐quarter to one‐half of purchases in the US are made through personal networks (Granovetter, 2005). McKinnon and Schröder (2006) found that in the context of attitudes towards consumer credit Eastern and Southern Europeans in particular tended to mention the loss of traditional family values as a cause of the rise in consumer debt. Respondents generally expressed suspicion and distrust of institutional lenders, with Eastern and Southern Europeans tending to borrow from their inner circle of family and friends.…”
Section: Review Of the Literaturementioning
confidence: 99%